2019
DOI: 10.3390/jcm8122131
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Pathway and YAP Signaling Alterations in Squamous Cancer of the Head and Neck

Abstract: Head and neck cancer affects the upper aerodigestive tract and is the sixth leading cancer worldwide by incidence and the seventh by cause of death. Despite significant advances in surgery and chemotherapy, molecularly targeted therapeutic options for this type of cancer are scarce and long term survival rates remain low. Recently, comprehensive genomic studies have highlighted the most commonly altered genes and signaling pathways in this cancer. The Hippo-YAP pathway has been identified as a key oncogenic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 126 publications
2
35
0
Order By: Relevance
“…Copy number amplifications of 11q22 and 3q25 (where YAP1 and WWTR1 are located, respectively) are common events reported in OSCC, often in mutual exclusive manner ( Campbell et al, 2018 ; Wang et al, 2018 ). These two genes are the major effectors negatively regulated by the Hippo pathway that is increasingly reported to play multiple roles in carcinogenesis, as reviewed comprehensively in recent years ( Dey et al, 2020 ; Santos-de-Frutos et al, 2019 ). However, the majority of the studies focused on either one of the paralogs or had assumed similar functions between paralogs ( Santos-de-Frutos et al, 2019 ; Zanconato et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copy number amplifications of 11q22 and 3q25 (where YAP1 and WWTR1 are located, respectively) are common events reported in OSCC, often in mutual exclusive manner ( Campbell et al, 2018 ; Wang et al, 2018 ). These two genes are the major effectors negatively regulated by the Hippo pathway that is increasingly reported to play multiple roles in carcinogenesis, as reviewed comprehensively in recent years ( Dey et al, 2020 ; Santos-de-Frutos et al, 2019 ). However, the majority of the studies focused on either one of the paralogs or had assumed similar functions between paralogs ( Santos-de-Frutos et al, 2019 ; Zanconato et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These two genes are the major effectors negatively regulated by the Hippo pathway that is increasingly reported to play multiple roles in carcinogenesis, as reviewed comprehensively in recent years ( Dey et al, 2020 ; Santos-de-Frutos et al, 2019 ). However, the majority of the studies focused on either one of the paralogs or had assumed similar functions between paralogs ( Santos-de-Frutos et al, 2019 ; Zanconato et al, 2016 ). Emerging evidence demonstrate that YAP1 and WWTR1 have distinct roles where they partner with different transcription factors, drive different downstream effectors and also modulate the tumor microenvironment distinctively ( Callus et al, 2019 ; Janse van Rensburg et al, 2018 ; Kaan et al, 2017 ; Plouffe et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A proposed model in head and neck SCC (HNSCC) ( Figure 2 F) suggests that FAT1 acts as a scaffold for Hippo kinases, favoring the activation of the complex and the phosphorylation of Yes-associated protein (YAP), which is sequestered in the cytoplasm or degraded. Absence of FAT1 dismantles the Hippo core complex, leading to YAP dephosphorylation and its translocation to the nucleus, where it interacts with TEAD to induce the expression of genes promoting tumor progression [ 42 ].…”
Section: Established Scc-associated Markersmentioning
confidence: 99%
“…A number of reports using cell lines have also suggested that YAP and TAZ play a critical role in cancer pathogenesis in several cancer types, including HNSCC 73,74 . RNAi-mediated depletion of YAP and TAZ interferes with the proliferation, survival, colony-forming ability, and migration of aggressive OSCC cells 55,56,58,60 .…”
Section: The Role Of Yap and Taz In Hnsccmentioning
confidence: 99%